2017
DOI: 10.1002/hast.796
|View full text |Cite
|
Sign up to set email alerts
|

Should Clinicians Set Limits on Reproductive Autonomy?

Abstract: As a gynecologic surgeon with a focus on infertility, I frequently hold complex discussions with patients, exploring with them the risks and benefits of surgical options. In the past, we physicians may have expected our patients to simply defer to our expertise and choose from the options we presented. In our contemporary era, however, patients frequently request options not favored by their physicians and even some they've found themselves online. In reproductive endocrinology and infertility, the range of op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Relatedly, it is observed that because ART treatment has a relatively high failure rate, is distressing for many, and is associated with significant drop-out rates, a patient-centred approach is crucial ( Dancet et al , 2011 ). Furthermore, it is noted that the ever-increasing array of treatment options and pressures upon couples makes the ‘best’ treatment in a specific situation difficult to ascertain ( King, 2017 ). For this reason, shared decision-making is seen as critical for ensuring that context-specific decisions are respectful of couples’ individual circumstances, which in turn leads to increased treatment variation ( Ezugwu and der Burg, 2015 ; Brabers et al , 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…Relatedly, it is observed that because ART treatment has a relatively high failure rate, is distressing for many, and is associated with significant drop-out rates, a patient-centred approach is crucial ( Dancet et al , 2011 ). Furthermore, it is noted that the ever-increasing array of treatment options and pressures upon couples makes the ‘best’ treatment in a specific situation difficult to ascertain ( King, 2017 ). For this reason, shared decision-making is seen as critical for ensuring that context-specific decisions are respectful of couples’ individual circumstances, which in turn leads to increased treatment variation ( Ezugwu and der Burg, 2015 ; Brabers et al , 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…Yet it also has its critics, including several other authors in this special report. As Louise King considers, a bald, hands‐off approach to autonomy can sometimes have the effect of abandoning patients at just the moment when they most need guidance and advice . And as Kimberly Mutcherson argues, a hands‐off, negative‐rights approach can be insufficient to support a right as fundamental as the right to procreate, leading her to argue for a positive legal right to financial assistance for assisted reproductive technologies …”
Section: Autonomy In Bioethicsmentioning
confidence: 99%